If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4x + -6x + 8x = 9 + 4 Combine like terms: x + -4x = -3x -3x + -6x + 8x = 9 + 4 Combine like terms: -3x + -6x = -9x -9x + 8x = 9 + 4 Combine like terms: -9x + 8x = -1x -1x = 9 + 4 Combine like terms: 9 + 4 = 13 -1x = 13 Solving -1x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = -13 Simplifying x = -13
| 21r^2-20r+18=0 | | -2x(x+1)=4 | | t(n)=4.5*1-8 | | 18+b=-14 | | -8p=48 | | -7(6+9m)-3m= | | 3n^2-14n-49=0 | | 5(3-2y)+4y=-6y | | 2.25x^2-8x+7=0 | | 1.8/0.02 | | ln(y-1)+ln(x+1)=2 | | 5n+3=7n-3 | | -3x(x+2)=2 | | 5x+3y=334 | | -4+(-6)-(-4)-(-7)= | | 2+1+x-6=0 | | 3n^2-14n-45=0 | | -76+45= | | -48+55= | | 81+(-90)= | | 6(x-4)=-4(x+1)+46 | | 2y^2=3y+7 | | -7(6+9m)-3= | | -50+-20= | | 3m^2-13m+8=0 | | -56+-4= | | 8(0.25+0.125y)-y=2 | | 4(x+2)=8(x-2)-4 | | 4(x-2)=-5(x+4)+45 | | -42-3= | | 6x^2-12x-8=10 | | 4x+5-2x=7+4x-6 |